Health education improve behavior and self-efficacy on personal hygiene among children with intellectual disability - Titiek Hidayati; Akrom Akrom; Indri Nurasa; Erviana Erviana (International Journal of Public Health Science (IJPHS), 2019)
Personal hygiene is one of the basic human needs and must be kept clean, including scalp and hair, eyes, nose, ears, nails of hands and feet, skin and overall body care. Health education on personal hygiene is still concern not only for healthy children but also for children with disabilities. One of the ways is with audiovisual methods. This study aimed to analyze the effect of health education on personal hygiene with audiovisual methods. The study design used was pre-experiment without a control group. The number of samples was 30 using total sampling technique. Knowledge of personal hygiene before health education (pre-test) was mostly insufficient category, after being given health education (post-test) mainly was in proper group. The pre-test attitude was in low category, and the post-test was still the same. Pre-test and post-test of behavior were mostly being practiced. Pre-test and post-test of self-efficacy were in low category. There was an influence of health education on personal hygiene with audiovisual methods on the level of knowledge in intellectually disabled children (p<0.05), but there was no effect on attitudes, behaviors, and self-efficacy in intellectually disabled children.